Application of Creative Ecology Theory to Concepts of Smart and Sustainable City as Possible Solution to Urban Development Problems – Case of Riga - BACULÁKOVÁ, Kristína (Journal of Environmental Management and Tourism; Vol 7 No 4 (2016): JEMT Volume VII Issue 4(16) winter 2016DO - 10.14505//jemt.v7.4(16).05, 2017)
Problematic of environment protection in the urban development is becoming crucial as the cities are growing faster and face the problem to maintain the quality of life of its citizens. In recent years, cities started to adopt plans for smart and sustainable development, which should combine effective solutions for all aspect of urban problems. In our paper, we choose the case of Riga, Latvia. It´s urban development plan belongs to one most highly-rated in Europe. We try to evaluate the plan according to the principles of newly introduced concept of creative ecology and analyse if the city’s plan really offers feasible solution for variety of recent urban problems.